2016
DOI: 10.1039/c6nr01524g
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state electrochemistry on the nanometer and atomic scales: the scanning probe microscopy approach

Abstract: Energy technologies of the 21st century require understanding and precise control over ion transport and electrochemistry at all length scales – from single atoms to macroscopic devices. This short review provides a summary of recent works dedicated to methods of advanced scanning probe microscopy for probing electrochemical transformations in solids at the meso-, nano- and atomic scales. Discussion presents advantages and limitations of several techniques and a wealth of examples highlighting peculiarities of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 173 publications
(269 reference statements)
1
29
0
Order By: Relevance
“…In recent times, ions have attracted much attention because of the significant role they play in energy related devices, sensors, information processing, and neuromorphic systems . However, the current trend of all‐solid electrochemical devices requires a synergistic approach to the fulfillment of nanotechnology dreams with a deeper understanding and precise control of the nanoscale material properties . Although researchers demonstrated single‐atom devices by sophisticated nanotechnology, those are still at the research and development stage and are not yet available for real device manufacturing.…”
mentioning
confidence: 99%
“…In recent times, ions have attracted much attention because of the significant role they play in energy related devices, sensors, information processing, and neuromorphic systems . However, the current trend of all‐solid electrochemical devices requires a synergistic approach to the fulfillment of nanotechnology dreams with a deeper understanding and precise control of the nanoscale material properties . Although researchers demonstrated single‐atom devices by sophisticated nanotechnology, those are still at the research and development stage and are not yet available for real device manufacturing.…”
mentioning
confidence: 99%
“…1 ,f proves that we can induce a local change in the conductivity of the layer when the tip is scanned with a negative polarity, which we relate to the presence of mobile Li ions in the LMO film. This effect, which has been already shown for other mixed ionic–electronic conductors, represents an interesting starting point to obtain local electrochemical information from the sample using C-AFM [ 6 ]. Indeed, the biased tip induces a strong electric field (localized under the tip) inside the material, thus triggering a field-induced ionic migration of the Li ions which, if mobile, start to accumulate at the tip–sample interface.…”
Section: Resultsmentioning
confidence: 59%
“…This puts the outcome of our work in context of a wide range of applications. These pending problems pose severe challenges for the physical characterization of battery materials such as the local correlation between a nanoscale stimulus and the resulting dynamically evolving material response [ 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In situ IVz spectroscopy (i.e., local I–V and Δ z–V measurements) was introduced to study irreversible processes, for which the basic ESM method was found to be insufficient . This technique has been widely utilized in analyses of irreversible electrochemical processes in lithium‐ion conducting glass ceramic (LICGC) with negligible electronic conductance .…”
Section: Energy Storage Devicesmentioning
confidence: 99%